ESTIMATING ABOVEGROUND BIOMASS AND CARBON SEQUESTRATION FOR NATURAL STANDS OF QUERCUS AEGILOPS. IN DUHOK PROVINCE - & et al., Obeyed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The study was aimed to develop above ground biomass(AGB) and its component models for an individual tree and stand of Quercus aegilops The benefits of this study are to know the amount of forest biomass to help us to estimate the amount of the lost or emitted carbon during deforestation and will give a clear idea of the forest capacity in capturing and storing carbon C in the forest ecosystem.. The study was conducted in six locations in the northeastern Duhok province in Kurdistan region of Iraq. Twenty-one trees were selected according to their diameter classes and felled to measure fresh weight (FW) and dry weight (DW) from different organs, including (stem, branches, leaves, and whole tree). In addition to, all trees with diameter at breast height (D ≥5 cm) in 89 plots of 0.04 ha, each was measured. Allometric equations of individual trees were used for estimating AGB and its component depending on D only. The DW of AGB and its components were converted into C by multiplying it on a half. The AGB estimated for FW and DW of the entire study area are 157.5285, 115.1153 (Mg ha-1) respectively. The results showed that Csequestration in the stands for stems, branches, leaves and the whole tree are 146.005, 73.9333, 31.38121and 249.9924 Mg ha-1 respectively.